The components of life : from nucleic acids to carbohydrates - Rogers, Kara (Biochemistry, cells, and life, 2011)
The building blocks of all lifehuman and otherwiseare basic chemical molecules common to all organisms that simultaneously unite all species and set them apart. Together, nucleic acids, amino acids, proteins, lipids, and carbohydrates determine our genetic makeup, power our movements, and generally enable some of the most vital and complex chemical reactions of the body. This volume examines the structure and function of each of these fascinating elements and the interrelationships between them, which nurture all existence